Asymptomatic bacteriuria in pregnancy: systematic reviews of screening and treatment effectiveness and patient preferences. Issue 3 (13th March 2019) - Wingert, Aireen; Pillay, Jennifer; Sebastianski, Meghan; Gates, Michelle; Featherstone, Robin; Shave, Kassi; Vandermeer, Ben; Hartling, Lisa
Abstract : Objective: To systematically review screening and treatment effectiveness, and patient preferences, to inform recommendations by the Canadian Task Force on Preventive Health Care on screening for asymptomatic bacteriuria in pregnancy. Design: We searched multiple databases (inception to September 2017) and grey literature sources for studies on screening effectiveness and patient preferences. For treatment with antibiotics, we searched three databases for systematic reviews and obtained search results of the Cochrane Pregnancy and Childbirth Group's Trials Register to update a Cochrane review. Study selection, risk of bias assessment and evaluation of the quality for each outcome using Grading of Recommendations Assessment, Development and Evaluation was completed independently by two reviewers with consensus. Meta-analysis was conducted when appropriate as were analyses based on planned subgroup variables. Outcomes: For screening and treatment effectiveness: maternal and perinatal mortality, maternal and neonatal sepsis, pyelonephritis, spontaneous abortion, preterm delivery, low birth weight and serious adverse events. Valuation of outcomes for patient preferences. Results: Four studies compared outcomes before and after the introduction of a screening programme or between different screening programmes. All evidence on screening effectiveness was considered very low quality. Women have conflicting opinions about antibiotic use during pregnancy. Fifteen trials compared antibiotic treatment with no treatment or placebo in women with confirmed bacteriuria. Low-quality evidence found that treatment lowered rates of pyelonephritis (12 trials, relative risk [RR] 0.24; 95% CI 0.13 to 0.42; absolute risk reduction [ARR] 17.6%; number needed to treat [NNT] 6, 95% CI 5 to 7) and low birth weight (seven trials, RR 0.63; 95% CI 0.45 to 0.90; ARR 4.4%; NNT 23, 95% CI 15 to 85). Conclusions: Antibiotic treatment for women having significant bacteriuria likely reduces the incidence of pyelonephritis and low birth weight, but we are uncertain about the magnitude of the effect and about the extent to which we can apply these results to asymptomatic populations and screening programmes. PROSPERO registration number: CRD42016045263.